Randomized clinical trial evaluating the frequency of membrane sweeping with an unfavorable cervix at 39 weeks - Chauhan SP; Warner WB; Magann MI; Poole AT; Doherty DA; Magann EF; Putnam K (Dove Medical Press, 2011)
Kathleen Putnam1, Everett F Magann2, Dorota A Doherty3, Aaron T Poole1, Marcia I Magann2, William B Warner1, Suneet P Chauhan41Department of Obstetrics and Gynecology, Naval Medical Center – Portsmouth, Portsmouth, Virginia, USA; 2University of Arkansas for Medical Sciences, Little Rock, Arkansas, USA; 3School of Women's and Infants' Health, University of Western Australia, Perth, Australia; 4Aurora Healthcare, West Allis, Wisconsin, USABackground: Despite the widely accepted use of membrane sweeping to prevent postmaturity pregnancies, the optimal frequency for this procedure has not been established.Aim: To determine if the frequency of membrane sweeping in women with an unfavorable cervix at term results in fewer labor inductions.Methods: This was a randomized trial of women with an unfavorable cervix (Bishop's score of ≤4) at 39 weeks randomized into three groups: control, once-weekly membrane sweeping, and twice-weekly membrane sweeping.Results: Between January 2005 and June 2008, 350 women were randomized into the study (groups: control [n = 116], once weekly[n = 117], and twice weekly [n = 117]). Randomization of Bishop's score was different between groups (P = 0.019), with 67%, 71%, and 83% of control, once-, and twice-weekly groups, respectively, having scores of 3–4. There was no difference in the unadjusted rate of labor induction between the groups (35% versus 27% versus 23%, P = 0.149), and after the adjustment for the randomization of Bishop's score (adjusted odds ratio [OR] = 0.73, 95% confidence interval [CI] 0.41–1.29 and OR = 0.65, 95% CI 0.36–1.18 for once- and twice-weekly groups, respectively). A Bishop's score of 3–4 at randomization was the only statistically significant factor that decreased the likelihood of induction at 41 weeks (OR = 0.42, 95% CI 0.25–0.69).Conclusion: Frequency of membrane sweeping does not influence the likelihood of remaining undelivered at 41 weeks of pregnancy. The Bishop's score at around 39 weeks is the important factor as a predictor of the duration of pregnancy, and further studies would be required to determine whether membrane sweeping influences pregnancy duration.Keywords: labor induction, postmaturity pregnancy, Bishop's score, pregnancy duration